A United Nations' Sustainable Development Goals perspective for sustainable textile and apparel supply chain management. (September 2020) - Cai, Ya-Jun; Choi, Tsan-Ming
Highlights: Examine sustainable fashion supply chain management following SDGs. Conduct a systematic review and classification of the literature. Establish a balanced sustainable development scheme. Discuss managerial implications and future research. Abstract: Motivated by United Nations' Sustainable Development Goals (SDGs) and the importance of sustainability, this study examines how the textile and apparel (TA) supply chains can comply with the SDGs. By examining the literature as well as industrial practices, we show that the current sustainable operations in TA industry are far away from realizing the goals of economic growth going hand-in-hand with the social and environmental sustainability. For instance, among the SDGs, the goals of " Responsible Consumption and Production ", " Clean Water and Sanitation ", and " Climate Action " receive a considerable amount of attention, while goals of " No Poverty ", " Reduced Inequalities ", " Life below Water " and " Life on Land " have the least attention. Balanced sustainable development actions from the stakeholders' perspective are proposed. Managerial implications and future studies are discussed.